Aplikasi Mikoriza Arbuskula Untuk Meningkatkan Serapan Fosfat, Pertumbuhan Dan Produksi Tanaman Bawang Merah (Allium ascalonicum L.) - Muhammad Mujibur Rahman; Akhmad Rizalli Saidy; Chatimatun Nisa (EnviroScienteae, 2019)
One of the problems in phosphate nutrient fertilization is a low level of efficiency, so the application of arbuscular mycorrhiza is often done to increase phosphate uptake. In this study mycorrhizal was applied to shallots which were given P fertilizer to assess the effect of mycorrhizal applications on growth, yield, and phosphate uptake. This research was carried out at the Faculty of Agriculture's Greenhouse of the University of Lambung Mangkurat Banjarbaru from March to May 2016. The seed of shallot was grown on 5 kg of soil and quartz sand (3:1) fertilized by P (0, 50, 100, 150, 200 and 250 kg SP-36 ha-1) and applied with mycorrhiza (without and with 10 g of plant-1 mycorrhizal inoculum) at planting. The observations made after 75 days after planting showed that the application of arbuscular mycorrhiza was effected to improve several observation variables, namely plant dry weight, bulb dry weight, phosphate nutrient uptake, and phosphate efficiency. The application of mycorrhiza at phosphate doses of 250 kg SP-36 ha-1 can increase plant dry weight by 97% and bulb dry weight by 203% compared to without mycorrhiza. Whereas the application of mycorrhiza at a phosphate dose of 100 kg SP-36 ha-1 is the best and most efficient treatment to increase phosphate nutrient uptake and phosphate efficiency. The results of this study show that the application of mycorrhizal can increase nutrient uptake of phosphate which ultimately increases the growth and production of shallot plants.